Characterization of Znq+–imidazole (q = 0, 1, 2) organometallic complexes: DFT methods vs. standard and explicitly correlated post-Hartree–Fock methods1. Issue 22 (14th June 2015) - Boussouf, K.; Boulmene, R.; Prakash, M.; Komiha, N.; Taleb, M.; Mogren Al-Mogren, M.; Hochlaf, M.
<x xml:space="preserve">Abstract</x> Benchmarking DFts for the characterization of the Znq+–imidazole (q = 0, 1, 2) complexes.